Comparison of text-messaging to voice telephone interviews for active surveillance of adverse events following immunisation. Issue 31 (17th July 2015) - Regan, A.K.; Blyth, C.C.; Tracey, L.; Mak, D.B.; Richmond, P.C.; Effler, P.V.
Highlights: We compared adverse event information collected by text messages to telephone interview. Response rate was 40% higher to text messages compared to telephone interview. Women were more 60% more likely to report an adverse event by telephone interview. Data collected by text message were significantly timelier. Results indicate text messaging is a feasible method for rapid vaccine safety surveillance. Abstract: Objectives: In 2013, the Follow-up and Active Surveillance of Trivalent Influenza Vaccine in Mums (FASTMum) program began using short message service (SMS) to collect adverse event information in pregnant women who recently received trivalent influenza vaccine (TIV). This study was designed to compare data collected via SMS and telephone for the purposes of monitoring vaccine safety. Methods: A number of 344 women who received TIV were randomly assigned to a telephone interview group. They were telephoned seven days post-vaccination and administered a standard survey soliciting any adverse events following immunisation (AEFI) they experienced. They were matched by brand of vaccine, age group, and residence to 344 women who were sent a SMS seven days post-vaccination. The SMS solicited similar information. AEFI reported by SMS and telephone interview were compared by calculating risk ratios. Results: Response rate was higher to SMS compared to telephone interview (90.1% vs. 63.9%). Women who were surveyed by SMS were significantly less likely to report an AEFI compared to women who were surveyed by telephone (RR: 0.41; 95% CI: 0.29–0.59). The greatest discrepancies between SMS and telephone interview were for self-reported injection site reactions (3.1% vs. 16.8%) and unsolicited (or "other") events (11.4% vs. 4.1%). Data collected by SMS was significantly timelier. Conclusions: Data collection by SMS results in significantly improved response rates and timeliness of vaccine safety data. Systems which incorporate SMS could be used to more rapidly detect safety signals and promote more rapid public health response to vaccine quality issues.